Communication Analysis Through Computer-Mediated Communication on the Instagram Account @Widyhartono - Eka Fitri Qurniawati; Setiawan, Harry; Hero, Eko; Putri, Indah Mardini (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2025)
In this digital age, interpersonal communication has been shifted massively to social media, including the culinary field, which is inseparable from the role of food vloggers. Widy Hartono, a local food vlogger, is notable for his ability to build rapport with his followers through informative, personal, and consistent content. The purpose of this study was to examine communication practices through computer-mediated communication on the Instagram account @widyhartono, owned and managed by Widy Hartono. The descriptive qualitative research method was employed in this study through data collection techniques, including interviews, observations, and documentation. The results showed that, according to Social Information Processing Theory, three key aspects had emerged. The first was interpersonal communication, which reflected an interest in using social media. In publishing information, Hartono's Instagram account tends to emphasize a friendly persona and nonverbal communication online through emoticons. The second aspect was the interpersonal perspective, reflected in regular publishing content that presented a friendly and approachable persona. The third one was hyper-personal communication, where Widi Hartono argued that communication carried out using social media and face-to-face is identical, depending on the individual's personality and the context in which the message is conveyed. In conclusion, the strategy analysis for using Instagram by @widyhartono was to provide information that is more enjoyable and easier for the audience to understand, to approach the audience on social media so that they don't get bored, and to stay consistent in publishing and following a specific schedule for the content to be published.